2022
DOI: 10.1371/journal.pone.0274077
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-skin invasion is a reliable risk factor for poor prognosis in superficial soft tissue sarcomas

Abstract: Introduction Superficial soft tissue sarcomas are often left untreated unless they invade the skin and skin ulcers manifest. Progressive sarcomas frequently result in dismal oncological outcomes despite multidisciplinary treatment. This study aimed to identify prognostic factors for superficial soft tissue sarcomas. Materials and methods This study retrospectively analyzed the clinicopathological data of 82 patients with superficial soft tissue sarcomas treated between August 2003 and December 2020 at our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown higher rates of metastasis at presentation, increased rates of amputation, and higher rates of local recurrence in fungating groups when compared with their nonfungating tumor control groups. [27][28][29] Similarly, 5-year overall survival for patients with a fungating sarcoma is as low as 15.5% compared with 65.6% for nonfungating tumors. 28 Tumor ulceration and invasion of the skin is associated with worse overall survival, which further underpins the importance of prevention and early identification.…”
Section: Differences In Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown higher rates of metastasis at presentation, increased rates of amputation, and higher rates of local recurrence in fungating groups when compared with their nonfungating tumor control groups. [27][28][29] Similarly, 5-year overall survival for patients with a fungating sarcoma is as low as 15.5% compared with 65.6% for nonfungating tumors. 28 Tumor ulceration and invasion of the skin is associated with worse overall survival, which further underpins the importance of prevention and early identification.…”
Section: Differences In Outcomesmentioning
confidence: 99%
“…28 Tumor ulceration and invasion of the skin is associated with worse overall survival, which further underpins the importance of prevention and early identification. 29 In general, outcomes and prognosis after amputation of STS fungating masses are modest, with a poor overall survival. Palliative amputation decreases pain scores, improves mobility after amputation, and improves emotional and psychological well-being.…”
Section: Differences In Outcomesmentioning
confidence: 99%
See 1 more Smart Citation